2020
DOI: 10.3390/met10010155
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Segregation Behavior of Impurity by Electromagnetic Stirring in the Solidification Process of Al-30Si Alloy

Abstract: Increasing the removal efficiency of impurities during non-equilibrium solidification of hypereutectic Al-Si alloy remains a great challenge for the upgrading of metallurgical silicon (MG-Si) to solar grade Si (SOG-Si). Hence, a manageable method was provided to enhance the segregation behavior of impurities at the interface front of primary Si/Al-Si melt by introducing a rotating magnetic field (RMF) in the present work. Experimental results showed that electromagnetic stirring can improve the removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The currently observed Si separation in specimens, without stirring, supports findings regarding the important role of the occurring temperature gradient [88][89][90], whereas Si reduction under RMF seems to result from secondary azimuthal flow and the Si crystal movement. The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center.…”
Section: Reduction Of Si Crystalssupporting
confidence: 84%
See 2 more Smart Citations
“…The currently observed Si separation in specimens, without stirring, supports findings regarding the important role of the occurring temperature gradient [88][89][90], whereas Si reduction under RMF seems to result from secondary azimuthal flow and the Si crystal movement. The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center.…”
Section: Reduction Of Si Crystalssupporting
confidence: 84%
“…The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center. In the current study, the observed reduction in Si crystals may come from flows reducing the temperature gradient in the melt throughout the sample, and as presented in [88][89][90], the gradient appears to be important. The effects of the temperature gradients, cooling rate and strength of magnetic field require more investigations.…”
Section: Reduction Of Si Crystalsmentioning
confidence: 52%
See 1 more Smart Citation
“…Then a secondary flow in the meridional plane appears, resulting from the imbalance between centrifugal force and radial pressure gradient (Figure 8a). Although the secondary flow condition is relatively weak, comprising only approximately 30% of the primary flow condition [32], it plays an important role in improving the transport of the solute atoms in the axial direction of the Al-Si melt. With cooling proceeding, the heat preferentially escapes through the bottom of the crucible, and thereby, the temperature gradient in the Al-30Si melt is formed.…”
Section: Electromagnetic Separation Mechanism Of Primary Simentioning
confidence: 99%
“…In recent years, an important new technique called high magnetic field (HMF) processing has been applied to material processing as a non-contact method [12][13][14], especially during solidification [15,16], which contributes to the influencing of secondary particle migration/orientation [17] and liquid metal motion and convection [18,19] to achieve more accurate control over the microstructure of materials [20,21]. The development of superconductivity technology has made it easy to obtain HMF of 10 T and above, which has promoted the application of HMFs in materials science and engineering and is therefore regarded as a new opportunity in this field [22,23].…”
Section: Introductionmentioning
confidence: 99%